The Theory of Didactic Situations as a Methodology for Teaching Mathematical Modeling - Sacaquirín, Mateo (2025)
[Objective] The main objective of this research was to measure the impact on academic performance of a teaching proposal for mathematical modeling of functions using Brousseau’s theory of didactic situations. [Methodology] A quantitative study with a pre-experimental design was conducted with a sample of 22 high school students belonging to the Remigio Crespo Toral Educational Unit (Ecuador). Previously, the participants followed a conventional study routine on the topics of function modeling. A pretest was then administered to evaluate the group’s academic performance. Subsequently, eight work sessions were conducted during which the didactic situations were implemented. Finally, a posttest was administered to evaluate the results after the intervention. [Results] The results of a descriptive analysis of the grades showed an 87% improvement in posttest scores, and the results of a student’s t-test analysis showed a significant difference between the pretest and posttest scores (p-value < 0.05). Furthermore, it was confirmed that the theory of didactic situations is compatible with the modeling cycle by strengthening various modeling competencies, such as the use of graphs and algebraic language. [Conclusions] It was shown that mathematical modelling using didactic situations significantly improved academic performance.